The Magnetic Structure of NiFe2O4 Nanoparticles - Kamzin, A. S.; Bingolbali, A.; Dogan, N.; Yesil, Z.; Asilturk, M. (PLEIADES PUBLISHING LTD, 2019)
The Mossbauer studies of the magnetic structure of nickel ferrite (NiFe2O4) nanoparticles (NPs) are presented. It is shown that the redistribution of ions over nonequivalent crystallographic positions occurs upon a decrease in the size of NiFe2O4 crystallites to nanovalues, thus leading to the structural transformation of NiFe2O4 nanoparticles from inverse spinel to mixed spinel. It has been established that the magnetic moments of Fe ions in the volume of NiFe2O4 nanoparticles are ferromagnetically (collinearly) ordered, being noncollinear (or oblique) in the near-surface layer probably due to the frustration of moments in the near-surface layer of nanoparticles.
Keywords: magnetic nanoparticles (MNPs); ferrite spinel MNPs; magnetic structure of MNPs; Mossbauer spectroscopy; NONEQUILIBRIUM CATION DISTRIBUTION; CANTED SPIN ARRANGEMENT; NICKEL FERRITE; MOSSBAUER; POLYOL; Physics